Legal education and artificial intelligence: vectors of interaction - A. S. Danielyan (Russian Journal of Economics and Law, 2024)
Objective: to develop proposals for the introduction of artificial intelligence (AI) in legal education.   Methods: dialectical methods (analysis and synthesis, induction and deduction, systematization, comparison, classification, forecasting), statistical, formal-legal and comparative-legal methods. Used in combination, these methods allow comprehensive analysis of the relationship between AI and legal education.   Results: the article reveals the main directions to improve legal education in the conditions of AI development: integration of information and communication technologies and training of specialists able to work effectively at the intersection of law and technology. The advantages and disadvantages of using AI in legal education are identified. Ethical aspects of AI application are outlined, as well as the need to manage the development of technologies based on the principles of fairness, transparency and consideration of human interests. The author states the importance of developing not only specialized knowledge, but also universal competencies that will help students to adapt successfully to the dynamically changing conditions of professional activity.   Scientific novelty: a comprehensive analysis of the interaction between legal education and AI was carried out, including the identification of specific opportunities for the AI application in legal education, as well as related risks and problems. The author proposes a systematic approach to improving legal education in the context of AI development, focusing on theneed to revise educational programs in legal areas in terms of integrating information and communication technologies; developing universal competencies in students to adapt to a dynamically changing professional environment; introducing mandatory advanced training for judges, legal practitioners to develop skills for using AI systems.   Practical significance: the study results can be used to optimize and adapt the educational programs of law schools to the digital era requirements and to develop effective approaches to the AI application in legal practice and education, taking into account ethical aspects and potential risks.